Assessment of Natural Radioactivity Levels and Estimation of Radiation Dose by Inhalation Environmental Air Samples from Hanoi - Anh Le, Hoang; Viet Thanh, Do; Duy Linh, Bui (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4, 2021)
This study investigates radioactivity in the ambient air for a district in Hanoi capital, Vietnam, in the period 2015 - 2018. Aerosol samples are collected by Taifful (Тайфун, Russia) equipment, using ΦПП 15-3p filter, to determine the 40 K, 238 U, and 232 Th concentration by gamma spectrometry method and following the STI/DOC 010/295 TRS 295-IAEA-1989 guidelines. While the Radon concentration level is directly determined by the Pylon portable radiation monitors (model AB-5R). Results show that the 40 K isotopes, 238 U, 232 Th, and Radon concentration levels are 40.43 ± 8.88 µBq.m -3 , 4.39 ± 0.47 µBq.m -3 , 2.01 ± 0.13 µBq.m -3 , and 20.63 ± 1.06 Bq.m -3 respectively. The total annual effective dose for people of different age groups caused by radioactive isotopes ranges from 0.73 mSv.year -1 to 0.84 mSv.year -1 . Those levels are lower than the current national standards and regulations of many cities in the world. The study can be used as an initial reference for the recommendation of regulation development for Vietnam in near future.